Electrical installations for open-cast mines and quarries Part 3. Recommendations for equipment and ancillaries (BSI, 1988)
Electrical equipment, Outdoor electric equipment, Electrical installations, Mining equipment, Mines, Quarries, Design, Selection, Rotating electric machines, Transformers, Static convertors, Interrupters (circuit-breakers), Occupational safety, Electric cables, Earth conductors, Safety devices, Colour codes, Electric conductors, Flexible cables, Bending, Electric connectors, Control devices, Drums (materials handling equipment), Control equipment, Leakage currents, Fault currents, Earthing, Circuits, Switchgear, Fire safety, Fire-escape routes, Electrical safety, Enclosures, Industrial electrical installations, Electric machines, Electrical components, Fire alarms, Fire detectors, Firefighting equipment, Fire extinguishers